2022
DOI: 10.1021/acsagscitech.2c00034
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Acidification as a Methane Mitigation Strategy for Manure Management

Abstract: Excreta from housed animals are typically stored before land application, and storage is an important point source of CH4, N gases, and odor. This study explored acidification as a strategy for greenhouse gas (GHG) mitigation, specifically the potential to reduce the acid dose to improve cost-effectiveness and minimize environmental impacts. Pig slurry was stored with five doses of concentrated sulfuric acid [1.2–6.0 kg (m3 of slurry)−1] for 63 days. Emissions of CH4 and NH3 were reduced by 46–96% and 33–78%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…Early summer acidification with sulfuric acid was reported to reduce slurry methane emission from the storage of pig slurry by 95% and is an alternative to anaerobic digestion. Ma et al also reduced methane emission by >95% using low-dose acidification with 6 kg sulfuric acid m –3 slurry . However, Ma et al discussed that the inhibition effect might be overcome by the methanogenic community at such low doses of sulfuric acid and it is unclear whether the slurry needs to be repeatedly acidified multiple times during a season to sustain the inhibitive effect .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early summer acidification with sulfuric acid was reported to reduce slurry methane emission from the storage of pig slurry by 95% and is an alternative to anaerobic digestion. Ma et al also reduced methane emission by >95% using low-dose acidification with 6 kg sulfuric acid m –3 slurry . However, Ma et al discussed that the inhibition effect might be overcome by the methanogenic community at such low doses of sulfuric acid and it is unclear whether the slurry needs to be repeatedly acidified multiple times during a season to sustain the inhibitive effect .…”
Section: Resultsmentioning
confidence: 99%
“…Ma et al also reduced methane emission by >95% using low-dose acidification with 6 kg sulfuric acid m –3 slurry . However, Ma et al discussed that the inhibition effect might be overcome by the methanogenic community at such low doses of sulfuric acid and it is unclear whether the slurry needs to be repeatedly acidified multiple times during a season to sustain the inhibitive effect . By combining slurry funnels with acidification methods that reduce methane by >95% in the storage, net methane emission reduction (in-house and storage emission) could exceed 90%.…”
Section: Resultsmentioning
confidence: 99%
“…Petersen et al (2012) vonden bij toevoeging van sulfaat en vergelijkbare methaanemissiereductie als bij met zwavelzuur aangezuurde mest. Voor het effect van aanzuren op methanogene populaties zie Ottesen et al, 2009;Peterson et al, 2012;Habtewold et al, 2018;Chen et al, 2019;Ma et al, 2022. In mestvergisters wordt onder andere gestuurd op een pH van circa 7-8 om een optimale methaanproductie te krijgen. Bij een hoge belasting met veel makkelijk afbreekbaar organisch materiaal ontstaat een ophoping van vetzuren waardoor de pH daalt en daardoor worden de methanogene micro-organismen die deze vetzuren afbreken geremd.…”
Section: Methaanunclassified
“…18 Leaching of S can affect the mobility of phosphorus contributing negatively to the environment. Odor emissions are a concern of the acidification technology, but Ma et al 11 observed reduced odor emissions from sulfuric acid-treated slurry. Hansen et al 19 showed a 90% reduction in emissions of H 2 S by in-house acidification, whereas other emissions of other odorants were increased.…”
Section: Introductionmentioning
confidence: 99%
“…Often slurry storage tanks will develop a natural crust, and comparison with emissions from a liquid open slurry surface may not be realistic . Acidification of slurry is a topic of high interest since it can reduce NH 3 and CH 4 emissions by up to 78 and 96%, respectively, ,, from slurry storage. Acidification can take place anywhere in the slurry management chain, e.g., in-house, in storage tanks, or during field application .…”
Section: Introductionmentioning
confidence: 99%